Alpha particle transport in the presence of ballooning type electrostatic driftwaves. (15th June 2015) - Nishimura, Y.; Huang, B.; Cheng, C. Z.
Abstract: Employing Hamiltonian mechanics, the transport of fusion born alpha particles in the presence of driftwave turbulence is investigated. An analytical turbulence model based on the toroidal drift eigenmode is employed for guiding center orbit-following calculations. It is shown that high energy particles are less susceptible to driftwave turbulence. The passing particle transport is due to overlapping of guiding center electric islands whose widths are inversely proportional to the square root of the parallel velocity. For trapped particles, through a coordinate transformation from the poloidal angle and the parallel velocity to the action-angle variables, the resonance between the bounce motion and the toroidal precession motion, which can cause secondary island formation in the phase space, is demonstrated.